Gomphosphenia plenkoviciae sp. nov. A new species from Crveno jezero, Croatia - Udovič, Marija Gligora; Žutinić, Petar; Piltaver, Ivna Kavre; Kulaš, Antonija; Ozimec, Roman; Tofilovska, Slavica (Phytotaxa, 2018)
Crveno jezero (Red Lake) is one of the largest karstic sinkhole lakes in the Europe. Diatom flora of this lake was unknown due to difficulties in collecting samples. Recently, samples were collected by speleodivers in the frame of systematical natural sciences research, during the cave diving expedition “Crveno jezero 2017” and observations revealed the existence of a new species, Gomphosphenia plenkoviciae Gligora Udovič & Žutinić sp. nov. The species is described herein as new to science based on light and scanning electron microscopy. Gomphosphenia plenkoviciae is characterized by having narrowly clavate to linear valves, which are slightly heteropolar in larger specimens to clavate in smaller specimens, thus differing from the closest taxon by the valve outline and shape of the central area. Smaller valves of G. plenkoviciae differ from other small-sized Gomphosphenia species by valve outline, striae morphology and the shape of axial and central areas.